Accurassay Laboratories: State-of-the-Art Automation of the TSMC Iron Ore Lab - Brad McBain (Canadian Institute of Mining, Metallurgy and Petroleum, 2013)
Agenda ? Accurassay Laboratories and Automation ? History and experience ? Features and benefits of automation in the lab ? Tata Steel Minerals Canada (TSMC) Iron Ore Laboratory ? State-of-the art systems and design ? The integration of fusion systems and XRF units ? Meeting deliverables: quality, reliability, safety